Mobile data services : an insight to its adoption and future direction - Gan, Jimmy Cher Wen (2008)
Mobile data service in Singapore is in the midst of moving to 3G network access. Despite the promising forecast for MDS initially, MDS has not attracted a critical mass of local users. Therefore, it is essential that local telecommunication operators understand the adoption of WAP services when developing mobile commerce.